Digital Supply Chain Management in the Tourism and Hospitality Industry: Trends and Prospects - Tatyana B. Klimova; Irina V. Bogomazova; Ekaterina V. Anoprieva; Irina V. Semchenko; Roman V. Plokhikh (International Journal of Supply Chain Management, 2020)
Abstract— The article discusses the basics of the digital supply chain management, its characteristic features and scope of application are covered. The analysis of a condition of development of digital supply chain management in the world reflecting growth of its share in gross domestic product, and the Russian Federation for which characteristic is the state initiative of advance and development of digital processes, but not business structures is carried out. The role of the Internet of things within digitalization of supply chain management is considered, in this regard the optimistic and conservative forecast of structure of the market of the Internet of things till 2025 is submitted. In work characteristic of information space of the sphere of tourism is given, the digital services and platforms which were widely adopted and succeeded offices of the tourist companies are described. The offered model of the digital platform for the sphere of tourism and hospitality of the Russian Federation «Tourism 4.0» with the description of the principles, characteristic of it, can be provided as a result of a combination of key technological capabilities, namely artificial intelligence, the Internet of things, robotization, voice technologies, a supply chain management. The presented «digital funnel» reflects the place of the tourism and hospitality industry among the participants in the digitalization market. Results of a research allowed to distinguish the factors constraining and keeping development of modern technologies in the industry, to reveal trends and regularities in the short term.